Possibility of Producing Ethanol from Moringa Oleifera Pod Husk - Ali, Eman N.; M. Z., Jamaludin (Akademi Baru, 2015)
Moringa oleifera is a plant which benefits to mankind from its root until leaves. From food to biofuel, all parts are useful to human being’s daily life. In this research, the pod husk was examined to determine the possibility of producing ethanol. The pod husk were dried and used with two sizes; one is grinded to get powder, and the other is cut within 5 x 5 x 2 mm. About 10 grams of Moringa oleifera pod husk was put into conical flask and distilled water was added up to 250 mL. The pre-treatment was made by adding an alkaline solution of NaOH, the pH of the sample was adjusted to (4.5, 5.0, and 5.5) using H2SO4. The samples were autoclaved at temperature of 120oC for 2 hours then, the samples were cooled to room temperature (25+/-2oC). Baker’s yeast (Saccharomyces cerevisae) was prepared with different concentrations of (1g, 5g, and 10g) and added to the samples for fermentation process which took place in the incubator shaker at temperature of 36oC, and for a period of 72 hours. The bioethanol concentration was measured using High Performance Liquid Chromatography (HPLC) with refractive index detector and REZEX ROA-Organic Acid HPLC Column using 0.05 N H2SO4 as the mobile phase. The bioethanol produced from Moringa oleifera pod husk was 8.400 g/L using 1g/L yeast, and the ferementartion took place at pH 4.5 for the sample size of 5 x 5 x 2 mm. The results showed that Moringa oleifera pod husk can be introduced as a new material for bioethanol production in Malaysia and other tropical countries where this tree is available.